Invasive Cervical Cancer After a Positive Pap Test Result and Negative Human Papillomavirus Test Result. Issue 4 (October 2021) - Locke, Alexander; Shah, Nina R.; Fetterman, Barbara; Poitras, Nancy; Wi, Soora; Castle, Philip E.; Wentzensen, Nicolas; Kinney, Walter; Clarke, Megan A.; Lorey, Thomas
Abstract : The majority of cervical cancers after Pap test–positive, human papillomavirus test–negative co-tests are symptomatic or clinically apparent.